2018
DOI: 10.14419/ijet.v7i2.11295
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flexural and impact strength of carbon nanotube reinforced AA7075 metal matrix

Abstract: Metal matrix nano-composites are grabbing more attention by many researchers in the recent years as they exhibit outstanding properties when compared to pure metal alloys. In the present study Aluminium Alloy 7075 was selected as the matrix and carbon nanotubes was selected as reinforcing element to investigate the percentage enhancement of flexural strength and impact strength of metal matrix composite. Stir casting process was selected to fabricate the specimens. The multi walled carbon nanotubes with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…18 This preheating step is used to enhance wettability, eliminate moisture content, and remove surface impurities. 12 The experimental setup for the stir casting process is employed to develop the AA7075/Si 3 N 4 /TiB 2 HMMCs as shown in Figure 1. Figure 2 displays the stir casting furnace used in the HMMCs fabrication.…”
Section: Fabrication Of Hybrid MMCmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This preheating step is used to enhance wettability, eliminate moisture content, and remove surface impurities. 12 The experimental setup for the stir casting process is employed to develop the AA7075/Si 3 N 4 /TiB 2 HMMCs as shown in Figure 1. Figure 2 displays the stir casting furnace used in the HMMCs fabrication.…”
Section: Fabrication Of Hybrid MMCmentioning
confidence: 99%
“…The optimization of the weight fraction of Al 2 O 3 nanoparticles in the composite is crucial for achieving optimal mechanical behavior. Ghazanlou and Eghbali 11 and Rao et al 12 highlighted the effect of the type of reinforcement used in AA7075 metal matrix composites on mechanical properties. The experiment found that Al7075/CNT composites have better mechanical properties than the Al7075/GNP composites, while the incorporation of CNTs led to a significant improvement in impact and flexural strength by 125% and 90%, respectively, compared to the base alloy.…”
Section: Introductionmentioning
confidence: 99%